Long‐term lava extrusion after the 2011 Shinmoe‐dake eruption detected by DInSAR observations. Issue 16 (25th August 2014) - Miyagi, Yousuke; Ozawa, Taku; Kozono, Tomofumi; Shimada, Masanobu
Abstract In January 2011, the latest eruption began at Shinmoe‐dake volcano, Japan, and lava accumulated in the crater. Differential interferometric synthetic aperture radar (DInSAR) observations after the end of main eruption indicated continuous uplift on the lava surface. We estimated the volume increase of lava, and the volume change rate has decreased exponentially. Results from long‐term DInSAR processing indicate slow subsidence outside the crater. We interpret that this subsidence is caused by deflation of a shallow source located beneath the crater, which is a reaction to the extrusion of lava. Between November 2011 and May 2013, the total volume of extruded lava within the crater is estimated to be 6.7 ± 0.1 × 104 m3, which is comparable to the deflation volume of the shallow source. The system is not closed within the shallow source to the crater; thus, long‐term lava extrusion can be explained by continuous injection from a deeper source to the shallow source.